2014
DOI: 10.4319/lo.2014.59.4.1310
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide turnover in permeable river sediment

Abstract: We measured nitric oxide (NO) microprofiles in relation to oxygen (O 2 ) and all major dissolved N-species (ammonium, nitrate, nitrite, and nitrous oxide [N 2 O]) in a permeable, freshwater sediment (River Weser, Germany). NO reaches peak concentrations of 0.13 mmol L 21 in the oxic zone and is consumed in the oxic-anoxic transition zone. Apparently, NO is produced by ammonia oxidizers under oxic conditions and consumed by denitrification under microoxic conditions. Experimental percolation of sediment cores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…To determine the effect of higher Fe 2+ on chemodenitrification in Mesoproterozoic oxyclines, we modeled N 2 O production rates at Fe 2+ concentrations of up to 10 mM—near the predicted upper limit for Proterozoic oceans (Derry, ). We varied NO concentrations from 10 pM, the lower range in modern OMZ oxyclines (Ward & Zafiriou, ), to 500 nM, the maximum concentration measured in modern sediments (Schreiber, Polerecky, & De Beer, ; Schreiber, Stief, Kuypers, & De Beer, ). Our rate law suggests that 1–5 nM N 2 O day −1 production rates would be possible in modern oxyclines with >1 nM NO and >10 μM Fe 2+ (Babbin et al., ) via solely abiotic reactions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of higher Fe 2+ on chemodenitrification in Mesoproterozoic oxyclines, we modeled N 2 O production rates at Fe 2+ concentrations of up to 10 mM—near the predicted upper limit for Proterozoic oceans (Derry, ). We varied NO concentrations from 10 pM, the lower range in modern OMZ oxyclines (Ward & Zafiriou, ), to 500 nM, the maximum concentration measured in modern sediments (Schreiber, Polerecky, & De Beer, ; Schreiber, Stief, Kuypers, & De Beer, ). Our rate law suggests that 1–5 nM N 2 O day −1 production rates would be possible in modern oxyclines with >1 nM NO and >10 μM Fe 2+ (Babbin et al., ) via solely abiotic reactions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Measured NO concentrations in modern ferruginous systems are highly variable but can reach up to 500 nM e.g. in anoxic sediments (Schreiber et al, 2008(Schreiber et al, , 2014. In these settings NO may be produced as a by-product of microbial denitrification or chemodenitrification, but is also an intermediate of nitrification and ammonium oxidation (Kuypers et al, 2018).…”
Section: Would Inhibition By No Be Expected In Modern and Ancient Environments?mentioning
confidence: 99%
“…Zafiriou and McFarland (1981) suggested that photochemically produced NO is a potential source of atmospheric NO during daylight. Apart from the photochemical production, various microbial pathways of NO have been identified including denitrification, nitrification and anammox (Schreiber et al, 2014;Martens-Habbena et al, 2015;Caranto and Lancaster, 2017;Kuypers et al, 2018). Additionally, NO is a messenger molecule in marine organisms: phytoplankton does not only response to exogenous NO (Zhang et al, 2005), but also produce NO during their growth (Zhang et al, 2006a, b;Kim et al, 2006Kim et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%